Evaluación técnico-financiera para el proceso de obtención de aceite vegetal a partir de aguacate (Persea Americana) variedad Lorena (2018)
The objective of this project is the technical-financial evaluation for the process of extraction of avocado oil variety Lorena in order to make use of this in the cosmetic industry. To carry out the resolution of the objective it was necessary In the first part, collect bibliographic information about the avocado variety To study, it was identified that the physical and physicochemical characteristics more important to determine were: weight, pulp content, real density, apparent density, porosity, pH, humidity and volatile matter, fat content and dry material. The methods of extracting avocado oil were established by means of a PUGH decision matrix where the criteria that were considered critical for both the project and the industry to thus, extract oil by two of the methods found in the literature. For the extraction method by solvents Petroleum Ether (40-60) was used following the Technical Standard Colombian (NTC 6240), for the method of extraction by cold pressing used a suitable caulking gun to simulate the press process, a once the oil was extracted, the analyzes were carried out by means of a contracted service physicochemical and microbiological indicated by resolution 1418 of 2011 for oils used in the cosmetic industry and thus, determine which of the oils obtained by the two methods is more apt for the intended use.